\[\boxed{\text{796\ (796).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[y( - 9) = - \frac{2}{3} \cdot ( - 9) = 2 \cdot 3 = 6\]
\[y( - 6) = - \frac{2}{3} \cdot ( - 6) = 4\]
\[y( - 3) = - \frac{2}{3} \cdot ( - 3) = 2\ \]
\[y( - 2) = - \frac{2}{3} \cdot ( - 2) = \frac{4}{3} = 1\frac{1}{3}\]
\[\text{\ y}( - 1) = \frac{2}{3}\]
\[y(0) = 0\]
\[y(1) = - \frac{2}{3}\]
\[y(2) = - 1\frac{1}{3}\]
\[y(3) = - 2\ \ \]
\[y(6) = - 4\]
\[x\] | \[- 9\] | \[- 6\] | \[- 3\] | \[- 2\] | \[- 1\] | \[0\] | \[1\] | \[2\] | \[3\] | \[6\] |
---|---|---|---|---|---|---|---|---|---|---|
\[y\] | \[6\] | \[4\] | \[2\] | \[1\frac{1}{3}\] | \[\frac{2}{3}\] | \[0\] | \[- \frac{2}{3}\] | \[- 1\frac{1}{3}\] | \[- 2\] | \[- 4\] |
\[\boxed{\text{796.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 2\text{ab} - 3ab^{2} = \text{ab} \cdot (2 - 3\text{ab})\]
\[2)\ 8x^{4} + 2x³ = 2x³(4x + 1)\]
\[3)\ 12a²b² + 6a²b³ + 12a²b³ =\]
\[= 6ab²(2a + ab + 2b)\]
\[4)\ 2a - 2b + ac - bc =\]
\[= 2 \cdot (a - b) + c \cdot (a - b) =\]
\[= (a - b)(2 + c)\]
\[5)\ m² - mn - 4m + 4n =\]
\[= m(m - n) - 4 \cdot (m - n) =\]
\[= (m - n)(m - 4)\]
\[6)\ ax - ay + cy - cx - x + y =\]
\[= (ax - cx - x) - (ay - cy - y) =\]
\[= x(a - c - 1) - y(a - c - 1) =\]
\[= (a - c - 1)(x - y)\]